Dissertações defendidas no Programa de Pós-graduação em Geografia/UFMG no 1º semestre de 2016 (Revista Geografias, 2017)
Dissertações defendidas no Programa de Pós-graduação em Geografia/UFMG no 1º semestre de 2016